Revision of Ishigakia Uchida (Hymenoptera: Ichneumonidae: Acaenitinae) from Japan, with a new species having a close relative in South Africa - Ito, Masato; Maeto, Kaoru (Zootaxa, 2016)
Two Japanese species of the genus Ishigakia Uchida, 1928, i.e., the type species from Ryukyus, I. exetasea Uchida, and a new species from Honshu, I. albitarsa Ito & Maeto sp. nov., are (re-)described. Antennal tapping and oviposition behavior of female I. exetasea was observed on the stalks of Japanese silvergrass Miscanthus sinensis. The new species, I. albitarsa, has (presumably) close relatives from mainland China and, disjunctely, from South Africa. A key to the world species of Ishigakia is also provided.